2011
DOI: 10.1227/neu.0b013e31820777cf
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Ventral vs Dorsal Surgery for Cervical Spondylotic Myelopathy

Abstract: Surgery for treating CSM was followed by significant improvement in disease-specific symptoms and in HR-QOL. Greater improvement in HR-QOL was observed after ventral surgery. Dorsal fusion surgery was associated with longer length of hospital stay and higher hospital costs. The pilot study demonstrated feasibility for a larger randomized clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
84
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 27 publications
7
84
0
Order By: Relevance
“…A further 65 studies were subsequently excluded for the following reasons: single level CSM (n = 14); mean cervical kyphosis [15°( n = 1); OPLL related cervical myelopathy (n = 13); combination of anterior and posterior surgical approaches used (n = 5); different surgical indications between groups (n = 7); and non-controlled studies (n = 25). Hence, a total of 8 studies were included in the meta-analysis [21][22][23][24][25][26][27][28]. The detail selection process is shown in Fig.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further 65 studies were subsequently excluded for the following reasons: single level CSM (n = 14); mean cervical kyphosis [15°( n = 1); OPLL related cervical myelopathy (n = 13); combination of anterior and posterior surgical approaches used (n = 5); different surgical indications between groups (n = 7); and non-controlled studies (n = 25). Hence, a total of 8 studies were included in the meta-analysis [21][22][23][24][25][26][27][28]. The detail selection process is shown in Fig.…”
Section: Search Resultsmentioning
confidence: 99%
“…Edwards et al [23] Ghogawala et al [26] Hirai et al [27] Kristof et al [24] Liu et al [25] Wada et al [22] Yonenobu et al [21] Total (95% CI)…”
Section: Study or Subgroupmentioning
confidence: 99%
“…In a recent nonrandomized prospective study, Ghogawala et al [13] reported no difference in terms of functional recovery between patients who underwent anterior or posterior approach. The postoperative mJOA scores in both groups were nearly two points better compared with the preoperative mJOA scores (from 11.60 to 13.54 in the posterior group and from 13.40 to 15.44 in the anterior group).…”
Section: Clinical Improvementmentioning
confidence: 96%
“…A ventral approach allows for direct decompression of ventral pathological entities in kyphotic, neutral, or lordotic spines, and avoids the pain associated with a posterior paraspinal musculature stripping approach, but is associated with its own compli cations including dysphagia, hoarseness, and cardiopul monary events. 1,4,5,10,21 Traditional postoperative outcome measures such as complications, readmission rates, revision surgery rates, and return to work measures do not fully encompass the patient experience following surgery and the relative ad vantages and disadvantages of each of the approaches. Recent studies have increasingly investigated financial cost and QOL outcomes for these 2 surgeries.…”
mentioning
confidence: 99%
“…Recent studies have increasingly investigated financial cost and QOL outcomes for these 2 surgeries. 1,3,5,9,22 Despite the numerous studies on this topic, uncer tainty remains about which of the 2 procedures is optimal for the treatment of CSM. Previous reviews on the topic, including one in this journal, 13 have attempted to address this uncertainty by using physiological parameters and other preoperative factors that may aid in the selection of the optimal surgical approach.…”
mentioning
confidence: 99%